Grenada : Fifth Review Under the Extended Credit Facility, Request for Waivers of Nonobservance of Performance Criteria and Request for a Three-Year Arrangement Under the Extended Credit Facility, and Financing Assurance Review. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Fifth Review Under the Extended Credit Facility (ECF) for Grenada. Four of the six quantitative performance criteria for end-November 2009 were met. The primary balance, excluding the grants target, was missed by 3.3 percent of GDP owing to higher-than-expected expenditures related to donor-financed capital projects and overruns on current spending associated with a sharp rise in unpaid invoices less than 60 days old. The authorities are requesting waivers for the missed performance criteria based on their implementation of corrective measures.